Professional quality of life among physicians of tertiary care hospitals: An Egyptian cross-sectional study - Bassma Abdelhadi Ibrahim; Mona Mostafa; Sarah Mohamed Hussein (SAGE Publishing, 2021)
Background: Professional quality of life greatly impacts wellbeing and performance of professionals working in the field of caring. The study aims at assessing the components of professional quality of life and their predictors. Design and Methods: The cross-sectional study was performed on 167 physicians enrolled by using stratified random sampling from tertiary care hospitals, Ismailia, Egypt. It was conducted by a structured interview questionnaire which included Maslach Burnout Inventory to assess burnout syndrome, and Professional Quality of Life version 5 (Pro QOL- 5) subscale to assess compassion fatigue and satisfaction. Results: Among participants, 78.9% had high burnout, 76% had moderate potential compassion satisfaction and 82% had moderate potential compassion fatigue. The correlation between scales of professional quality of life scores showed significant results (p < 0.05). The multiple linear regression analysis showed that marital status, frequency of dealing with critical patients, and compassion fatigue score (B= -6.959, B= 3.573, B= 1.115) were significant predictors of burnout score (p < 0.05). Marital status (B= 2.280, p = 0.024), and burnout score (B = 0.179, p = 0.000) were significant positive predictors of compassion fatigue. While compassion satisfaction score was negative predictor (B= -2.804, p = 0.006). The predictors of compassion satisfaction were the marital status (B = 5.039, p = 0.000), and compassion fatigue score (B = -0.254, p = 0.006). Conclusion: High prevalence rates of burnout, compassion fatigue and satisfaction indicate poor professional quality of life were detected among physicians in tertiary care hospitals.